El Gallo Pinto Afro-Caribbean Rice and Beans Conquer the Costa Rican National Cuisine - Vega Jiménez, Patricia (2012)
This paper examines the historical origins of gallo pinto (spotted rooster) to show how a plebeian dish of black beans and rice came to be embraced as a symbol of Costa Rican national identity. Beans have been a basic staple in Central America since pre-Hispanic times, but although Spaniards planted rice in the sixteenth century, it became a significant part of the diet only in the nineteenth century as a result of the transition from subsistence agriculture to coffee exports. The combination of rice and beans was introduced in the nineteenth century by Afro-Caribbean migrant railroad workers. Notwithstanding elite self-perception of Costa Rica as a white, European nation, economic necessity during the Great Depression helped gallo pinto gain middle class acceptance. This case illustrates both the importance of social and economic history in shaping cultural symbols and also the ways that lower-class foods can become central to national identities.